2013
DOI: 10.1186/1471-2334-13-53
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study of HPV type prevalence according to age and cytology

Abstract: BackgroundA cross sectional study to investigate HPV prevalence according to age and cytology.MethodsWomen presenting to a gynaecological outpatient clinic for a Pap smear test were included in the study (n=3177). All women had cervical cytology and HPV testing.ResultsOverall prevalence of any 24 HPV type analysed was 33.1% (95% CI 31.5% to 34.7%) and HPV 16 and HPV 42 were the most frequent (6.7% (95% CI 5.8% to 7.6%), 6.8% (95% CI 5.9% to 7.6%)), in total samples. Multiple HPV infection rate was 12.9% (95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
44
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 22 publications
16
44
3
Order By: Relevance
“…In addition, many studies reported the prevalence of HPV infection varied according to age group (Coupe et al, 2008, Argyri et al, 2013, however others have not identified a significant relation (Burd 2003). Our results show that the prevalence of HPV infection were similar in all age groups.…”
Section: Discussionsupporting
confidence: 39%
“…In addition, many studies reported the prevalence of HPV infection varied according to age group (Coupe et al, 2008, Argyri et al, 2013, however others have not identified a significant relation (Burd 2003). Our results show that the prevalence of HPV infection were similar in all age groups.…”
Section: Discussionsupporting
confidence: 39%
“…Our results showed a significant association between HR HPV prevalence and epithelial abnormalities detected in cervical smears very similar to earlier reports (Argyri et al, 2013;Sarma et al, 2015). The current study detected HPV 16 viral DNA in 50% of LSIL, 75% of HSIL and 100% of SCC.…”
Section: Fast Transfer Analysis Cartridges For High Risk Hpv Desupporting
confidence: 93%
“…However, it has been observed that the presence of MT HPV does not affect the severity of infection, and HPV infections are independent of one another (39). In the present study, 43.40% of all HPV + participants were infected with one type of HPV (ST HPV), whereas the majority of participants exhibited MT HPV (56.60%).…”
Section: Discussionmentioning
confidence: 51%